Heat treated carbon supported iron(ii)phthalocyanine oxygen reduction catalysts: elucidation of the structure–activity relationship using X-ray absorption spectroscopy. Issue 48 (28th November 2016) - Miller, Hamish A.; Bellini, Marco; Oberhauser, Werner; Deng, Xin; Chen, Hengquan; He, Qinggang; Passaponti, Maurizio; Innocenti, Massimo; Yang, Ruoou; Sun, Fanfei; Jiang, Zheng; Vizza, Francesco
Abstract : Correlation between atomic structure and oxygen reduction activity by X-ray absorption spectroscopy. Abstract : This paper focuses on studying the influence of the heat treatment on the structure and activity of carbon supported Fe(ii )phthalocyanine (FePc/C) oxygen reduction reaction (ORR) catalysts under alkaline conditions. The FePc macrocycle was deposited onto ketjen black carbon and heated treated for 2 hours under inert atmosphere (Ar) at different temperatures (400, 500, 600, 700, 800, 900 and 1000 °C). The atomic structure of Fe in each sample has been determined by XAS and correlated to the activity and ORR mechanisms determined in electrochemical half cells and in a complete H2 /O2 anion exchange membrane fuel cells (AEM-FC). The results show that the samples prepared at 600 and 700 °C have the highest electrochemical catalytic activity for the ORR, consistent with the findings that the FeN4 active sites are thermally stable up to 700 °C, confirmed by both XANES linear combination fittings and EXAFS fittings. Upon annealing at temperatures above 800 °C, the FeN4 structure partially decomposes to small iron nanoparticles. The transition from the FeN4 structure to metallic Fe results in a significant loss in ORR activity and an increase in the production of undesirable HO2 − during catalysis.